Keterampilan Mengajar Guru Ekonomi Dan Lingkungan Sekolah Sebagai Determinan Terhadap Minat Belajar Ekonomi - Revita Yuni; Wilyam Jevons Alexius Siahaan (Journal of Psychology and Instruction, 2024)
The problem in this study is the low interest in learning in class X students of SMA Negeri 2 Percut Sei Tuan. This study aims to determine and see the effect of teacher teaching skills and the school environment on the learning interest of class X students of SMA Negeri 2 Percut Sei Tuan. This type of research is ex post facto. With a population of 288 students consisting of 8 classes, the sampling technique in this study was to use proportionate startified random sampling technique using the Slovin formula. In this technique, 168 students were sampled. Data collection techniques in this study were interviews, observation, documentation, and questionnaires. From the results of this study obtained multiple linear regression equation Y = 19.997 + 0.334X1 + 0.364X2. Based on the partial hypothesis test, it is obtained that the teacher's teaching skills (X1) are tcount > ttable (4.345 > 1.654) and a significant value of 0.000 <0.05. The school environment variable (X2) obtained a partial hypothesis test tcount > ttable (4.379 > 1.654) and a significant value of 0.000 <0.05. Simultaneously it also shows that there is a positive and significant influence of the teacher's teaching skills and the school environment on student learning interest which is shown thus Fcount > Ftable (35.346 > 3.05) and significant (0.000 <0.05). Based on the test the coefficient of determination was obtained at 0.300 or 30%. This shows that the variables of Teacher Teaching Skills (X1) and School Environment (X2) have a contribution of 30% to Student Learning Interest (Y) and the remaining 70% is influenced by other variables not explained in this study.